Enhancing the stability of sodium-ion capacitors by introducing glyoxylic-acetal based electrolyte - Andrea Hainthaler; Akshaya S. Sidharthan; Desirée Leistenschneider; Andrea Balducci (Journal of Power Sources Advances, 2024)
Sodium-ion Capacitors (SICs) are becoming increasingly important energy storage devices. This study presents an in-depth comparison of a largely used electrolyte for said application, sodium hexafluorophosphate in ethylene carbonate:propylene carbonate (NaPF6 in EC:PC), with the novel electrolyte sodium bis(trifluoromethanesulfonyl)imide in 1,1,2,2-tetraethoxyethane:propylene carbonate (NaTFSI in TEG:PC). Firstly, half-cells of the SIC standard electrode materials, hard carbon (HC) and activated carbon (AC), are shown to perform comparably well with the two electrolytes. However, the use of the novel electrolyte in SICs allows for an improved stability during float tests. All in all, the novel electrolyte NaTFSI in TEG:PC appears to be a very promising alternative electrolyte for SIC application.